Pertuzumab and trastuzumab as adjuvant treatment for HER2-positive early breast cancer: outcomes in Chinese patients in the APHINITY study. (23rd February 2021) - Shao, Zhimin; Tseng, Ling-Ming; Huang, Chiun-Sheng; Pang, Da; Yang, Youngsen; Li, Wei; Liao, Ning; Geng, Cuizhi; Zhang, Qingyuan; Xu, Binghe; Liu, Donggeng; Kwong, Ava; et al.
Abstract: Background: The addition of pertuzumab to trastuzumab plus standard chemotherapy as adjuvant therapy following surgery significantly improved invasive disease-free survival (IDFS) in patients with HER2-positive early breast cancer in the multinational randomized APHINITY trial (NCT01358877, BIG 4–11/BO25126/TOC4939G). We analyzed clinical outcomes in the subgroup of patients recruited at Chinese sites. Methods: Patients were randomized to standard adjuvant chemotherapy plus 1 year of trastuzumab with pertuzumab or placebo. Patients recruited in mainland China, Hong Kong and Taiwan are included in this descriptive analysis. Results: Chinese patients had similar demographic characteristics to the global population, but a higher proportion had nodal involvement. Although this subgroup analysis was not powered to detect statistical significance, a numerical improvement in IDFS was observed with the addition of pertuzumab to trastuzumab in Chinese patients (hazard ratio, 0.69; 95% confidence interval: 0.39–1.19; 3-year IDFS event-free estimates 92.5% [pertuzumab] and 91.7% [placebo]), which was consistent with the primary analysis of the global population. Further subgroup analyses showed numerical improvements in the Chinese node-positive, hormone receptor-negative and -positive subgroups, although confidence intervals were wide due to the low number of events. The incidence of diarrhea was higher in the pertuzumab arm, and no primary cardiac events occurred in Chinese patients in either arm. Conclusions: Pertuzumab, used in combination with trastuzumab and chemotherapy in APHINITY, is effective as an adjuvant treatment regimen for Chinese patients with HER2-positive early breast cancer in a setting with curative intent. The safety profile in Chinese patients was consistent with that of the global population. Abstract : In APHINTY, pertuzumab, trastuzumab and chemotherapy were effective as an adjuvant treatment regimen for Chinese patients with HER2-positive early breast cancer. Safety was consistent with that of the global population.